(3GdehGLgI GdLfGFjI dGfJgGc GdNUhUjI ef NdGd GdhSW GdeYdheGJj (B:s "(3OQGSI ebGQfI(B" / s - (3YHO Gddg eMeO YHO Gddg eMeO GdTMjs; (3CMeO YhV HdGds; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI(B:s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2023)
(3Sqgd GdJWhQ aj GdhSW GdeYdheGJj GQJcGH GdcKjQ ef GdLQGFe, hde JYO BKGQgG eMUhQI aj GdfWGb GdEbdjej dOhdI HYjfgG; GdCeQ GdPj HGJ jKjQ HYV GdJMOjGJ GdbGfhfjI hGdYedjI CeGe GdCLgRI GdeYfjI HecGaMI GdLQjeI (B((3CLgRI GdYOGdI GdLfGFjI HLejY eSJhjGJgG hYdi GNJdGa COhGQgG(B). (3hJJeKd GdLQjeI GdeYdheGJjI ai cd Sdhc ZjQ eTQhY Ch efGma ddCNdGb Ch ZjQ eSehM Hg jQJHW HGdeYGdLI GdBdjI ddHjGfGJ Ch HfbdgG, Ch ai CfgG GdCaYGd GdELQGejI GdfGJLI ef NdGd Ch HhGSWI GSJNOGe GdeYdheGJjI Ch GdJbfjI GdMOjKI GdeJeKdI ai GdceHjhJQ, Ch Cj ef GdhSGFW GdGdcJQhfjI GdCNQi(B. (3hjJe GfJgGc MQeI GdMjGI GdNGUI YHQ GdhSW GdeYdheGJj ef NdGd GdONhd Ydi ehbY HOhf JUQjM, Ch GdGSJjdGA hfTQ aMhUGJ WHjI Ch JTNjU WHj hSLdGJ WHjI Ch eGdjI Ch ZjQgG JNU GdZjQ, hcPdc JZjjQ JUGeje GdehbY GdNGU Hg Ch MPag, hCjkVG GSJQGb GdSeY Ch JSLjd Ch fbd Ch HK Ch EaTGA eMGOKGJ dg, hcPdc GdJbGW UhQ GdZjQ hfbdgG Ch cTagG (B... (3EdN(B. s
With the beginning of the spread of the international information network; There was no concern about crimes that could be committed on the Internet, given its limited use. But with the dawn of the information revolution, and the expansion of the use of the Internet, and the beginning of its use in commercial transactions, and the entry of all segments of society to the list of users; Information network crimes have appeared, and they have increased over time, and their forms and forms have varied, and they are called information crimes; That is, those criminal acts and deeds that are carried out through the international information network, and are considered one of the most important challenges and the most serious crimes facing the countries of the world in our time. Based on that; Information and communication technology is one of the technical means that is constantly evolving, especially when it is required to research how the crime was committed, know the perpetrators, and confront information crimes that occur on the computer and the information network, as well as the digital divide between countries, and the efficiency and cooperation of these countries among themselves about dealing with information technology.
(3CWQhMI (B((3OcJhQGg(B)-(3LGeYI GdbGgQI(B-(3cdjI GdMbhb(B-(3bSe GdbGfhf GdLfGFj, (B2023s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B277-295s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdbGfhf GdLfGFjs; (3GdMjGI GdNGUI s; (3JYQja GdhSW GdeYdheGJjs; (3JYQja Mb GdMjGI GdNGUgs; (3LQGFe JJYdb HGdGSJjdGAs; (3UhQ LQGFe cTa GdGSQGQs; (3LQjeg GSJQbGb GdSeYs; (3LQjeg GdJbGW GdUhQs; (3eGgjI GdGMGOjK GdJj jMejgG GdbGfhfs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs